2016
DOI: 10.1002/jemt.22674
|View full text |Cite
|
Sign up to set email alerts
|

The several elements of intestinal innate immune system at the beginning of the life of broiler chicks

Abstract: Functional capacity of digestive system and intestinal adaptive immunity are immature at hatching of broiler chicks. Therefore, intestinal innate immunity after hatching is vital to young chicks. The purpose of this study was to investigate expression and tissue distributions of several elements of the innate immune system (i.e., TLR2, TLR4, CD83, and MHC class II expressing cells) in the intestine of one-day-old chicks. For this purpose, ileum and cecum were examined the under different conditions, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…live weight by approximately 6 weeks. The breeding program has caused broilers to be very sensitive to stress and the related gut inflammation due to selection-associated metabolic disorders and immature immune system, mostly during the first few weeks of life [ 30 , 31 ]. Sub-therapeutic levels of antibiotics have been used as growth promotors in broiler production to prevent or control the incidence of clinical and subclinical diseases, such as necrotic enteritis caused by Clostridium perfringens , and increasing food digestion and nutrient absorption [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…live weight by approximately 6 weeks. The breeding program has caused broilers to be very sensitive to stress and the related gut inflammation due to selection-associated metabolic disorders and immature immune system, mostly during the first few weeks of life [ 30 , 31 ]. Sub-therapeutic levels of antibiotics have been used as growth promotors in broiler production to prevent or control the incidence of clinical and subclinical diseases, such as necrotic enteritis caused by Clostridium perfringens , and increasing food digestion and nutrient absorption [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of information, studies suggest that mucosal epithelial cells of birds, similar to mammals, actively participate in innate immune responses against harmful pathogens. Eren et al showed that IEC of day old chicks express both TLR4 and TLR2 [ 10 ], and additional studies showed that avian mucosal epithelial cells, including enterocytes, produce and secrete various antibacterial compounds which include lysozymes,β defensins, cathelicidins and avidin [ 11 16 ]. Moreover, it was shown that avian enterocytes obtained from orally BSA-immunized birds responded in an antigen specific manner to additional antigenic stimulus, and were suggested to be active participants in induction of intestinal anaphylaxis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The web of reticular fibres forming the stroma of the cecal tissue had the impression that the lymphoid cells filling in time. In the literature review, there was no evidence of the organization of the reticular fibres in the intestinal tissue except for the one‐day‐old chicks given the first section of this study (Eren et al, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…Thus, we hypothesized that innate immune system elements of chicks against antigens could be important at the beginning of their lives and the specific defence mechanisms are involved overtime after this initial period. To test this, we initially evaluated the composition of the innate immune system elements in the intestines of newly hatched chicks (Eren et al, 2016). We then investigated the histological development of CTs and the distribution of antigen-presenting cells with toll-like receptors within the first two weeks after hatching.…”
Section: Introductionmentioning
confidence: 99%